Unfinished Histories Empire and Postcolonial Resonance in Central Africa and Belgium - Fraiture, Pierre-Philippe (Leuven University Press, 2022)
Colonial memory and interdisciplinary memorialization across Congo, Rwanda, Burundi and Belgium Belgian colonialism was short-lived but left significant traces that are still felt in the twenty-first century. This book explores how the imperial past has lived on in Belgium, but also in the Democratic Republic of the Congo, Rwanda and Burundi. The contributing authors approach colonial legacies from an interdisciplinary perspective and examine how literature, politics, the arts, the press, cinema, museal practices, architecture, and language policies - but also justice and ethics - have been used to critically revisit this period of African and European history. Whilst engaging with significant figures such as Sammy Baloji, Chokri Ben Chikha, Gaël Faye, François Kabasele, Alexis Kagame, Edmond Leplae, VY Mudimbe, Fiston Mwanza Mujila, Joseph Ndwaniye, and Sony Labou Tansi, this book also analyses the role of places such as the AfricaMuseum, Bujumbura, Colwyn Bay, Kongolo, and the Virunga Park to appraise the links between memory and the development of a postcolonial present. Contributors: Sarah Arens (University of Liverpool), Robert Burroughs (Leeds Beckett), Bambi Ceuppens (AfricaMuseum), Matthias De Groof (University of Antwerp), Catherine Gilbert (University of Newcastle), Chantal Gishoma (University of Bayreuth), Hannah Grayson (University of Stirling), Dónal Hassett (University of Cork), Sky Herington (University of Warwick), Nicki Hitchcott (University of St Andrews), Yvette Hutchison (University of Warwick), Albert Kasanda (Charles University, Prague), Maëline Le Lay (CNRS/ THALIM, Sorbonne nouvelle), Reuben Loffman (Queen Mary University of London), Caroline Williamson Sinalo (University of Cork) Ebook available in Open Access. This publication is GPRC-labeled (Guaranteed Peer-Reviewed Content).